(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the necessity and factors of the emergence of cognitive linguistics, the studies conducted in this field and their subject and concepts, as well as the special role of concepts and concepts in these places are highlighted.